(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Backup: The problem of dry eye syndrome is of great importance and significance in ophthalmology. The purpose of the present paper was to study the effect of Lipoflavon on the course of inflammatory process in herpetic keratitis (HK ) patients with dry eye syndrome (DES). Material and Methods: Clinical study was performed in 40 patients with HK (superficial dendritic keratitis) and DES; additionally, we followed up 17 patients with HK. All patients were divided into two groups: Study Group included 15 HK and DES patients receiving Lipoflavon treatment; Control Group included 25 HK and DES patients receiving traditional treatment. The state of the cornea was scored by Draize criteria. The data obtained were statistically processed using SPSS 11.0 package. Results: Assessing the data obtained in the present study, it is arguable that Lipoflavon significantly decreases clinical signs in patients with HK and DES. Conclusions: Inclusion of Lipoflavon in the complex treatment of HK patients with DES significantly increases the efficacy of therapy that is evidenced by the fact that corneal epithelization and infiltrate dispersion are accelerated, and corneal edema and epitheliopathy of the cornea and conjunctiva are less apparent after treatment of patients in Study group as compared to control. The use of quercetin has a positive effect on qualitative and quantitative characteristics of tear production in patients with HK and DES, in particular, Schirmer test values are increased, tear break-up time is increased, conjunctival fold intensity is decreased and tear meniscus height is increased.